The VHL/HIF Axis in the Development and Treatment of Pheochromocytoma/Paraganglioma - Peng, Song; Zhang, Jun; Tan, Xintao; Huang, Yiqiang; Xu, Jing; Silk, Natalie; Zhang, Dianzheng; Liu, Qiuli; Jiang, Jun (Frontiers in Endocrinology, 2020)
Pheochromocytomas and paragangliomas (PPGLs) are rare neuroendocrine tumors originating from chromaffin cells in the adrenal medulla (PCCs) or extra-adrenal sympathetic or parasympathetic paraganglia (PGLs). About 40% of PPGLs result from germline mutations and therefore they are highly inheritable. Although dysfunction of any one of a panel of more than 20 genes can lead to PPGLs, mutations in genes involved in the VHL/HIF axis including PHD, VHL, HIF-2A (EPAS1), and SDHx are more frequently found in PPGLs. Multiple lines of evidence indicate that pseudohypoxia plays a crucial role in the tumorigenesis of PPGLs, and therefore PPGLs are also known as metabolic diseases. However, the interplay between VHL/HIF-mediated pseudohypoxia and metabolic disorder in PPGLs cells is not well-defined. In this review, we will first discuss the VHL/HIF axis and genetic alterations in this axis. Then, we will dissect the underlying mechanisms in VHL/HIF axis-driven PPGL pathogenesis, with special attention paid to the interplay between the VHL/HIF axis and cancer cell metabolism. Finally, we will summarize the currently available compounds/drugs targeting this axis which could be potentially used as PPGLs treatment, as well as their underlying pharmacological mechanisms. The overall goal of this review is to better understand the role of VHL/HIF axis in PPGLs development, to establish more accurate tools in PPGLs diagnosis, and to pave the road toward efficacious therapeutics against metastatic PPGLs.